Processing Options for Fat Content Reduction While Maintaining Sensory Characteristics of Koose - Osman, S. (University of Ghana, 2018)
Consumer preference for low fat content foods is increasing over the years. High fat content in most fried food products is a major factor affecting consumer acceptance of fried products today. Low-fat food products are becoming more popular, due to the health risk associated with the consumption of high fatty foods. Koose is a widely consumed street food in Ghana. It is prepared either by wet or dry milling of soaked and dehulled cowpea seasoned with salt, pepper and onions. A paste is obtained and deep fried in vegetable oil until a golden-brown crispy product is obtained. It is a good source of protein for regular consumers. However, the cooking method, deep frying leads to a very high fat content with its health risk to those who eat it regularly. This research focuses on pre-drying of the paste to reduce the initial moisture content, which is a known factor in increasing fat absorption. This study revealed processing options for fat content reduction of koose. The traditional koose processing (wet and dry milled) methods were used in producing koose. For wet milled samples, 500g of cowpea was soaked for 3hrs and dehulled. It was blended with 20g of seasoning ingredients to obtain a paste. For dried milled samples the cowpeas were soaked for 3 mins and dehulled, the dehulled cowpea was dried in a hot air oven at a temperature of 70ᵒC for 5hrs, and milled using a hammer mill with mesh screen size 1.0 mm to obtain a flour. About 200g of flour was mixed with 400 ml of water with 20g of seasoning ingredients to obtain a paste. For both processes the paste obtained was pre-dried at different temperatures (50ᵒC, 55ᵒC and 60ᵒC) and times (1, 2 and 3hrs). The pre-dried and the undried (as control) cowpea paste were fried at different temperatures/time. The pre-dried paste was fried at (160ᵒC, 170ᵒC, 180ᵒC / 10, 5, 1 minutes) and undried paste was fried at (160, 170, 180/ 15, 10, 5 minutes). After frying samples were presented to panellist to evaluate the sensory characteristics using a 150 mm hedonic scale from the least to the highest. Frying at a temperature 180ᵒC for 1mins for samples produced from the pre-dried cowpea paste and frying at 180ᵒC for 5mins samples produced from dry milled process, gave the least oil absorption for both pre-dried and undried paste. Samples produced from wet milling were spongier, soggier, and soft in appearance, for koose samples produced from predried and undried paste. Dry milled samples were hard and dry in appearance both for koose samples produced from pre-dried and undried paste. Wet milled koose samples were soft, spongier, and mushy in texture both for the pre-dried and undried samples. Dry milled samples were dry, hard, and flaky in texture for both pre-dried and undried samples. Wet milled koose samples were spongier, soggier, soft and mushy than the dry milled koose samples. Koose produced using dry milled processing method can be used to produce koose with reduced fat content. Koose samples produced from pre-dried paste absorbed less oil even at a lower temperature of frying. Further studies can be done to modify the texture of koose samples produced from pre-dried cowpea paste.
MPhil.
Keywords: Fat; Koose